Accounting Perspectives on Valuation of Intellectual Capital Versus Artificial Intelligence - Veronica GROSU; Alina BUTNARU (CIOBOTAR) Camelia-Cătălina MIHALCIUC; Cristina-Gabriela COSMULESE (Communications of International Proceedings, 2024)
In today's developing economy, it is clear that technology and human knowledge are creating new opportunities. The issue is not whether we use Artificial Intelligence (AI) systems, but how we value the assets generated by AI, how it interacts with the firm's Intellectual Capital (IC) and how we know which are the most important resources that increase productivity and add value. The efforts of accountants, academics, regulators, theorists and practitioners need to be directed towards resolving the uncertainties and issues related to the valuation and financial reporting of intangible assets generated by IA and IC. In this context, the exploration of the terms intellectual capital and artificial intelligence requires finding separate strategies for evolution, but with common principles. The most visible result is that there is an increased interest in artificial intelligence, but focused more on the technical, engineering parts, but not on the financial valuation of intangible assets. The academic community appreciates the advantages of technology to intellectual capital, but they draw attention to the need to recognize the intangibles that will create more and more species.
Keywords: valuation; intangible assets; artificial intelligence; intellectual capital.